Decreased Regional Homogeneity in Patients With Acute Mild Traumatic Brain Injury: A Resting-State fMRI Study. Issue 10 (October 2015) - Zhan, Jie; Gao, Lei; Zhou, Fuqing; Kuang, Hongmei; Zhao, Jing; Wang, Siyong; He, Laichang; Zeng, Xianjun; Gong, Honghan
Abstract : Abstract: Mild traumatic brain injury (mTBI) is characterized by structural disconnection and large-scale neural network dysfunction in the resting state. However, little is known concerning the intrinsic changes in local spontaneous brain activity in patients with mTBI. The aim of the current study was to assess regional synchronization in acute mTBI patients. Fifteen acute mTBI patients and 15 sex-, age-, and education-matched healthy controls (HCs) were studied. We used the regional homogeneity (ReHo) method to map local connectivity across the whole brain and performed a two-sample t- test between the two groups. Compared with HCs, patients with acute mTBI showed significantly decreased ReHo in the left insula, left precentral/postcentral gyrus, and left supramarginal gyrus ( p < 0.05, AlphaSim corrected). The ReHo index of the left insula showed a positive correlation with the Mini-Mental State Examination (MMSE) scores across all acute mTBI patients ( p < 0.05, uncorrected). The ReHo method may provide an objective biomarker for evaluating the functional abnormity of mTBI in the acute setting.